2013
DOI: 10.1255/ejms.1223
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Low-Molecular Weight Iodine-Terminated Polyethylenes by Gas Chromatography/Mass Spectrometry and Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry with the Use of Derivatization

Abstract: Gas chromatography/mass spectrometry (GC/MS) and matrix-assisted laser desorption/ionization time-of-flight (MALDI-ToF) mass spectrometry, in conjunction with various derivatization approaches, have been applied to structure determination of individual oligomers and molecular-mass distributions (MMD) in low-molecular mass polyethylene having an iodine terminus. Direct GC/MS analysis has shown that the samples under investigation composed of polyethyelene-iodides (major components) and n-alkanes. Exchange react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…M n values, calculated from 1 H NMR spectra of PE-I and from MALDI-TOF mass-spectra of preliminary derivatized iodoalkanes [38], are generally in good agreement (see supporting information). …”
Section: Accepted Manuscriptmentioning
confidence: 60%
See 1 more Smart Citation
“…M n values, calculated from 1 H NMR spectra of PE-I and from MALDI-TOF mass-spectra of preliminary derivatized iodoalkanes [38], are generally in good agreement (see supporting information). …”
Section: Accepted Manuscriptmentioning
confidence: 60%
“…Iodo-functionalized oligoethylenes (PE-I), which could be easily analyzed by 1 H NMR spectroscopy [4,5] and by mass spectrometry with preliminary derivatization [38], have been analogously synthesized at 40ºC, using co-catalysts 2, 4, 6 and different Nd:Mg ratios (Scheme 4).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Some of them have been given in the book 4 and described in our recent papers. [6][7][8] One of the important types of compounds that are produced synthetically or are present in living bodies and caustobioliths is organic sulfides. Although lowmolecular-weight sulfides have been studied many times by electron and chemical ionization mass spectrometry, the need in their analysis and profiling using ''soft'' ionization methods can arise.…”
Section: Introductionmentioning
confidence: 99%
“…The use of derivatization of analytes prior to analysis looks a very promising approach to enhance ionization efficiency and provide structural information. [1][2][3][4] Previously, we have shown that simple derivatization reactions such as silylation, acylation, alkylation, and imination were suitable for establishing some structural fragments of various types of analytes by MALDI-MS. [5][6][7][8][9] However, one of the most interesting derivatization techniques is based on the introduction of a fixed charge into an analyte molecule. [3,[9][10][11] Such methods are frequently used in combination with ESI-MS, in particular, for the analysis of peptides and proteins.…”
mentioning
confidence: 99%
“…[1][2][3][4] Previously, we have shown that simple derivatization reactions such as silylation, acylation, alkylation, and imination were suitable for establishing some structural fragments of various types of analytes by MALDI-MS. [5][6][7][8][9] However, one of the most interesting derivatization techniques is based on the introduction of a fixed charge into an analyte molecule. [3,[9][10][11] Such methods are frequently used in combination with ESI-MS, in particular, for the analysis of peptides and proteins. One of the first papers in this field has described the use of two-step derivatization of the N-terminus in peptides by acylation with iodoacetic anhydride, iodoacetic acid or other haloacyl halides followed by treatment with various amines or triphenylphosphine to form quaternary ammonium or phosphonium salts, respectively.…”
mentioning
confidence: 99%